WORK LIFE BALANCE PADA GENERASI Z YANG BEKERJA PART TIME - Erlina Vina Firnanda; Laila Listiana Ulya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The growing participation of Generation Z in part-time employment suggests that workplace flexibility does not necessarily lead to the attainment of work-life balance. While simultaneously managing academic responsibilities, financial needs, and social commitments, this generation faces complex challenges that require a clearer empirical understanding of how balance between work and personal life is maintained. This study examined the phenomenon using a quantitative descriptive approach involving 160 respondents aged 18–25 years who were selected through purposive sampling. Data were collected online using the Work-Life Balance Scale and analyzed through descriptive statistics. The findings revealed that 68.8% of the respondents demonstrated a moderate level of work-life balance, whereas 16.3% and 15.0% were classified as having high and low levels, respectively. Across the dimensions, Work Interference with Personal Life (WIPL) and Personal Life Interference with Work (PLIW) were found at a moderate level, while Work Enhancement of Personal Life (WEPL) and Personal Life Enhancement of Work (PLEW) were categorized as high. These findings indicate that work-life balance among young part-time workers is shaped more by their capacity to adapt to multiple roles than merely by minimizing conflicts between work and personal life. The study contributes to a broader understanding of work-life balance among Generation Z workers and provides a foundation for developing workplace environments that are more responsive to their characteristics and needs. ABSTRAK Fenomena meningkatnya keterlibatan Generasi Z dalam pekerjaan part-time menunjukkan bahwa fleksibilitas kerja tidak selalu berbanding lurus dengan tercapainya work-life balance. Di tengah upaya memenuhi kebutuhan ekonomi, pendidikan, dan kehidupan sosial secara bersamaan, kelompok ini menghadapi dinamika yang perlu dipahami melalui gambaran empiris mengenai keseimbangan antara pekerjaan dan kehidupan pribadi. Kajian ini memotret kondisi tersebut menggunakan pendekatan kuantitatif deskriptif terhadap 160 responden berusia 18–25 tahun yang dipilih melalui purposive sampling. Data diperoleh secara daring menggunakan Work-Life Balance Scale dan diolah dengan statistik deskriptif. Hasil analisis memperlihatkan bahwa 68,8% responden berada pada kategori sedang, sedangkan kategori tinggi dan rendah masing-masing mencapai 16,3% dan 15,0%. Pada tingkat dimensi, Work Interference with Personal Life (WIPL) dan Personal Life Interference with Work (PLIW) berada pada kategori sedang, sementara Work Enhancement of Personal Life (WEPL) serta Personal Life Enhancement of Work (PLEW) termasuk kategori tinggi. Pola tersebut mengindikasikan bahwa keseimbangan kehidupan kerja pada pekerja muda lebih banyak dibentuk oleh kapasitas beradaptasi dalam menghadapi berbagai peran daripada sekadar rendahnya konflik antara pekerjaan dan kehidupan pribadi. Temuan ini memperluas pemahaman mengenai karakteristik work-life balance pada pekerja Generasi Z sekaligus menjadi landasan bagi pengembangan lingkungan kerja yang lebih responsif terhadap kebutuhan mereka.